Does Father's Social Capital Matter to Child Undernutrition in Myanmar?. (November 2020) - Win, Thida; Tun Sein, Than; Ikeda, Wakaha; Morita, Akemi; Sokejima, Shigeru
This article examined the association between social capital of fathers and child undernutrition using a community-based survey in Myanmar in 2018. The anthropometric measurements of 1546 children aged 6 to 59 months and face-to-face interviews of 1546 respective biological fathers were performed. The three social capital indicators (institutional trust, social supports, and collective action) were included in 2-level logistic regression models for child wasting and child stunting. Social supports from fathers' social networks were protective measures for child wasting and child stunting at individual and community levels, respectively. The collective action of fathers was positively associated with child stunting at individual level. No association was found between institutional trust and both indicators of child undernutrition at all levels. The individual-level collective action on child stunting was conditional on the community-level social supports. Our findings suggest that existing nutritional strategies in Myanmar may be strengthened by targeting fathers to increase their support in child nutrition and by targeting the community to engage in the nutritional programs with their full support.